Identifikasi Diri dan Pembentukan Identitas Diri Karyawan dalam Proses Restrukturisasi Organisasi - mustadin taggala; Fathul Himam (Universitas Ahmad Dahlan, 2018)
Organization restructuring is a common phenomenon which is applied in order to improve organizational performance. Unfortunately, many restructuring processes often neglect their impacts on employees.This phenomenological research was directed to cover some issues related to the impact of organization restructuring on employees’ behavior, particularly on the way employees’ self identification were developed and how these experiences shape employes’ self identity. In-depth interviews were employed to collect the data that involved 10 employees from UIN Sunan Kalijaga Yogyakarta and UIN Sultan Alauddin Makassar as respondents. Phenomenology approach is used in this research, and the process of analyzing and interpreting data used Stevick-Colaizzi-Keen technique. Member checks and external audits were used to verify the trustworthiness of the data. This research concluded four major themes related to how employees’ self identity was developed and how employees put its meaning. The themes were (1) be a Learner; (2) surrender to his or her destiny; (3) being active and flexible; (4) be independent. These identities had unique implication toward employees’work behaviors in organization.